N-Terminal Prolactin-Derived Fragments, Vasoinhibins, Are Proapoptoptic and Antiproliferative in the Anterior Pituitary - Ferraris, Jimena (Public Library of Science, 2011)
The anterior pituitary is under a constant cell turnover modulated by gonadal steroids. In the rat, an increase in the rate of apoptosis occurs at proestrus whereas a peak of proliferation takes place at estrus. At proestrus, concomitant with the maximum rate of apoptosis, a peak in circulating levels of prolactin is observed. Prolactin can be cleaved to different N-terminal fragments, vasoinhibins, which are proapoptotic and antiproliferative factors for endothelial cells. It was reported that a 16 kDa vasoinhibin is produced in the rat anterior pituitary by cathepsin D. In the present study we investigated the anterior pituitary production of N-terminal prolactin-derived fragments along the estrous cycle and the involvement of estrogens in this process. In addition, we studied the effects of a recombinant vasoinhibin, 16 kDa prolactin, on anterior pituitary apoptosis and proliferation. We observed by Western Blot that N-terminal prolactin-derived fragments production in the anterior pituitary was higher at proestrus with respect to diestrus and that the content and release of these prolactin forms from anterior pituitary cells in culture were increased by estradiol. A recombinant preparation of 16 kDa prolactin induced apoptosis (determined by TUNEL assay and flow cytometry) of cultured anterior pituitary cells and lactotropes from ovariectomized rats only in the presence of estradiol, as previously reported for other proapoptotic factors in the anterior pituitary. In addition, 16 kDa prolactin decreased forskolin-induced proliferation (evaluated by BrdU incorporation) of rat total anterior pituitary cells and lactotropes in culture and decreased the proportion of cells in S-phase of the cell cycle (determined by flow cytometry). In conclusion, our study indicates that the anterior pituitary production of 16 kDa prolactin is variable along the estrous cycle and increased by estrogens. The antiproliferative and estradiol-dependent proapoptotic actions of this vasoinhibin may be involved in the control of anterior pituitary cell renewal.